The Role of Social Proof in The Decision-Making of The Rural Community Of Cirebon to Become Customers of Sharia Microfinance Institutions - Sukarnoto, Toto; Wartoyo; Cahyono, Heru (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2025)
The principle of social proof is one of the most powerful cognitive heuristics in decision making. This phenomenon is particularly relevant in the context of financial decision making, especially when individuals face uncertainty or complexity in financial product information. The purpose of this study is to describe the most dominant forms of social proof in encouraging the use of Islamic microfinance institutions in rural communities that are steeped in social and religious values. The research methodology uses a qualitative approach with a phenomenological design to gain an in-depth understanding of the experiences and perceptions of rural communities regarding social proof in their decision-making to become customers of Islamic microfinance institutions. The results of the study show that the role of religious leaders, the community, the community's experience interacting with Islamic financial institutions, the participation of microfinance institutions in the community, and the support of village officials and apparatus are able to motivate and convince the rural community to make decisions in transactions with Islamic microfinance institutions.